Access to Palliative Care in Low- and Middle-Income Countries during Coronavirus Disease-2019 Pandemic and Post-Pandemic Era: A Kenyan Experience - John Weru; Esther Nafula; Asaph Kinyanjui; Sriram Yennurajalingam (Palliative Medicine and Hospice Care, 2023)
The coronavirus disease-2019 (COVID-19) pandemic emphasized the role of palliative care as an essential service to patients and families affected by life-threatening illnesses. Challenges encountered included: patients were not able to access services due to lockdown or restricted movement, limited or no home-based care and visits, opioid analgesic supplies were depleted, high frequency of uncontrolled symptoms and psychosocial distress, limited patient-caregiver-clinician communication, reduced family interactions due to fear of infecting the already sick family members, few training opportunities for health care workers (HCW) and HCW distress and burn-out. To address these challenges, the following strategies were employed; utilization of digital technologies to match resources, innovation in provision of PC including adapting etiquette for patient care using digital technology, advocating policy changes, education, use of technology such as video calls among family members support for HCW.